Experimental investigation and techno-economic assessment of oilfield brine-derived carbonates for calcium looping CO2 capture - Rufan Zhou; Chunqing Jiang; Rafal Gieleciak; Lava Kumar Pillari; Lukas Bichler (Carbon Capture Science & Technology)
Flowback and produced water (FPW) from hydraulic fracturing operations of tight hydrocarbon reservoirs has attracted significant research interest, particularly regarding its treatment and the recovery of valuable minerals. In this study, a simple and sustainable method was developed to precipitate calcium (Ca), magnesium (Mg), and strontium (Sr) carbonates from a high salinity FPW using NH3 or NaOH and CO2-containing flue gas. The precipitated solids and the treated FPW solution were subjected to various characterization techniques to evaluate the properties of the solids and the efficiency of the precipitation method. The precipitated carbonate minerals were further investigated as sorbents for CO2 capture in the calcium looping process, demonstrating a substantial carbon capture capacity of approximately 0.3 kg CO2/kg solid sample. Moreover, a series of detailed process simulations and economic analysis were performed to further evaluate the potential of using solid precipitates from FPW in the calcium looping process. Two different operating modes and multiple cases of calcium looping using solid sorbents from FPW, integrated with renewable energy, were thoroughly studied. The economic analysis of this integrated technology showed a relatively comparable levelized cost of carbon capture, at less than $200 per tonne of CO2 captured. The techno-economic analysis of the overall process demonstrated the potential of the calcium looping process with carbonate precipitates from produced water as a possible approach for decarbonization and energy transition in the oil and gas industry.